THE INFLUENCE OF ACTIVITIES AND CHARACTERISTICS OF MANAGERS AND STRATEGIC ACTIONS ON BUSINESS RESULTS WITH THE MODERATION EFFECT OF IMPROVING KNOWLEDGE (example of Serbia) - Premović, Jelena; Jovsnović, Slavisa; Pavlović, Marko (Journal of Economic Development, Environment and People, 2025)
The paper analyzes the characteristics of companies, from the aspect of the organizational climate that prevails in them. The goal of authors was to determine to what extent there is a climate that encourages the exchange of knowledge, information and ideas. Also it was investigate to what extent the creativity and innovation of employees is encouraged. The main purpose of this paper is to investigate the influence of activities and characteristics of managers and strategic actions on business results with the moderation of improving knowledge in the companies in Serbia. The mutual relationship and influence of the analyzed variants of management activities and the manager's characteristics was determined through correlation analysis. Correlation analysis confirmed that there is an influence of activity variables and manager characteristics on variable strategic action. Correlation relations of the observed variants of management activities and the strategic action variable from the aspect of how ready the analyzed companies are to improve knowledge are listed. Based on the results of the regression analysis, a regression model was determined that singles out those activities and characteristics of managers that have the greatest impact on achieving the efficiency of strategic action, and singles out those variables of strategic action on which the greatest influence of the aforementioned variables is achieved.